Secular Nations under new gods : christianity's subversion by technology and politics - Vanderburg, Willem H. (UNIV OF TORONTO Press, 2018)
Ever since Max Weber's study of the role Protestantism played in our civilization, the role of Christianity in our world has been much debated. This work is addressed to those interested in a return to the Biblical message as opposed to what institutionalized Christianity has made of it.